Institutional Contexts and Corporate Diversification Strategy - Kong-Hee Kim (Journal of Management Research, 2024)
There has been a great deal of controversies concerning the performance implications of conglomerate (business group) strategy, often prevalent in emerging economies. The aim of this research is to develop a theoretical model that prescribes the viability of corporate diversification strategy in relation to institutional contexts. The theoretical model suggests that conglomerate strategy will be positively related to firm performance in institutional contexts where the functions of formal market controls and informal normative controls are inefficient, whereas focused/related diversification strategy will be positively related to firm performance in institutional contexts characterized by efficient market and normative controls. The framework synthesizing major theoretical perspectives will contribute to better understanding of the connection between institutional contexts and corporate diversification strategy.